Reconfiguration of space and human and territorial development in the Metropolitan Region of León Guanajuato - Susana Suárez (European Regional Science Association (ERSA), 2013)
Reconfiguration of space, and territorial and human development in the Metropolitan Region of Leon, Guanajuato, Mexico. Nowadays the urban and rural areas are experiencing deep transformations in their use, appropriation, in their economic activities, in the deployment of others, in their culture, in sum, in their social-territorial organization, all this as result of the spatial expansion of the capital. Is observed that in the rural areas there happen important process of industrialization and urbanization, equally it appreciates that in urban spaces significant changes are happening. Nevertheless, this does not mean that all the spaces acquire the same configuration, rather they present a great variety of expressions and inequality in terms of development, on one hand due to the fact that their conformation is a result of the interaction that takes place between the capitalist global dynamics and the conditions and answers of the local actors, and for other one due to the fact that the relocation of the productive and financial capital has deepened the economic already present disparities between the territories. These economic, social, cultural transformations and their repercussion in the reorganization of the urban and rural spaces, us lead us to raising the question how do these changes affect in her in the real capacity of the persons who inhabit these spaces to take decisions and actions, in his real opportunities to develop fully, to take the life that they want to take? What constitutes the human development according to Amartya Sen (1999) Equally they drive us to formulate the question how they reverberate in the possibility of join of the territories, in the viability of the construction of a social, economic, political and culturally integrated entity, in which there prevails the equity, the solidarity, the social justice, the social belonging and the adscription, which chases the territorial development, according to Rafael Echeverrí (2002:1) The intention of this paper is to initiate an analysis on the reconfiguration of the Metropolitan Region of Leon Guanajuato, Mexico that allows us the reflection on the repercussions of this reconfiguration in the human and territorial development of this zone, in order to start finding answers to our questions.
Keywords: 330; Reconfiguration space; human development; territorial development